Smart Governance and Smart Cities: A Review of The Literature - Yustiari, Shinta Happy (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2020)
An application based technology so called as smart city can be easily accessed by citizen and government. The government information could create safety and comfort in order to service better future life for their citizen. The main purpose of writing this paper is to gain an overview of the smart city concept using a qualitative approach, by a comprehensive review of the literatures. The conclusion from this paper could provide clear information from the most recently scientific articles focus on smart cities. This paper could be a basis for future researchers for another investigation.